Immunometabolism Modulation by Extracts from Pistachio Stalks Formulated in Phospholipid Vesicles - Simone Pani; Ilaria Pappalardo; Anna Santarsiero; Antonio Vassallo; Rosa Paola Radice; Giuseppe Martelli; Francesco Siano; Simona Todisco; Paolo Convertini; Carla Caddeo; Vittoria Infantino (Pharmaceutics, 2023)
Several studies have demonstrated the effectiveness of plant extracts against various diseases, especially skin disorders; namely, they exhibit overall protective effects. The Pistachio (Pistacia vera L.) is known for having bioactive compounds that can effectively contribute to a person’s healthy status. However, these benefits may be limited by the toxicity and low bioavailability often inherent in bioactive compounds. To overcome these problems, delivery systems, such as phospholipid vesicles, can be employed. In this study, an essential oil and a hydrolate were produced from P. vera stalks, which are usually discarded as waste. The extracts were characterized by liquid and gas chromatography coupled with mass spectrometry and formulated in phospholipid vesicles intended for skin application. Liposomes and transfersomes showed small size (<100 nm), negative charge (approximately −15 mV), and a longer storage stability for the latter. The entrapment efficiency was determined via the quantification of the major compounds identified in the extracts and was >80%. The immune-modulating activity of the extracts was assayed in macrophage cell cultures. Most interestingly, the formulation in transfersomes abolished the cytotoxicity of the essential oil while increasing its ability to inhibit inflammatory mediators via the immunometabolic citrate pathway.